2019
DOI: 10.3390/agronomy9050255
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of Sentinel-2 Leaf Area Index Data into a Physically-Based Crop Growth Model for Yield Estimation

Abstract: Remote sensing data, crop growth models, and optimization routines constitute a toolset that can be used together to map crop yield over large areas when access to field data is limited. In this study, Leaf Area Index (LAI) data from the Copernicus Sentinel-2 satellite were combined with the Environmental Policy Integrated Climate (EPIC) model to estimate crop yield using a re-calibration data assimilation approach. The experiment was implemented for a winter wheat crop during two growing seasons (2016 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…Based on these measurements, the model can be modified and used to make predictions about future states of the crop [9]. A range of different observations, either field measurements or derived from remote sensing, have been assimilated into crop models: phenology [10,11], soil moisture content [12][13][14][15][16][17], canopy cover [18,19], and, most-frequently used, leaf area index (LAI) [10,[14][15][16]18,[20][21][22][23][24][25][26][27][28]. Defined as the total one-sided area of leaf tissue per unit of ground surface area (provided in m 2 m −2 ), LAI is one of the key parameters in crop growth analysis due to its influence on light interception, biomass production, plant growth and ultimately on crop yield, and it is critical to understand the functioning of many crop management practices [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these measurements, the model can be modified and used to make predictions about future states of the crop [9]. A range of different observations, either field measurements or derived from remote sensing, have been assimilated into crop models: phenology [10,11], soil moisture content [12][13][14][15][16][17], canopy cover [18,19], and, most-frequently used, leaf area index (LAI) [10,[14][15][16]18,[20][21][22][23][24][25][26][27][28]. Defined as the total one-sided area of leaf tissue per unit of ground surface area (provided in m 2 m −2 ), LAI is one of the key parameters in crop growth analysis due to its influence on light interception, biomass production, plant growth and ultimately on crop yield, and it is critical to understand the functioning of many crop management practices [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The method is based on vegetation indices derived from spectral measurements and explained 78% of the LAI variability observed, slightly lower than the value achieved by the DL model developed in this study. Satellite images have also been used as inputs of an artificial neural network trained with radiative transfer models, PROSPECT (leaf optical properties model) and SAIL (canopy bidirectional reflectance model), to derive LAI maps in winter wheat (Novelli et al [69]). The authors obtained a coefficient of determination higher than 0.7 in two crop periods after comparing LAI estimates at ground level performed with the optical sensor LAI-2200 Plant Canopy Analyzer and satellite-derived observations.…”
Section: Novelty Of the DL Model Against Current Approaches Used For mentioning
confidence: 99%
“…Ref [13] assimilated Sentinel-2 derived LAI into the EPIC (Environmental Policy Integrated Climate) model to estimate winter wheat grain yield on Austrian experimental fields under four fertilization management strategies over the course of two growing seasons, using field-measured soil characteristics as model input. They found that assimilation via recalibration of parameters defining the LAI curve improved the model's performance notably during the first year (RMSE 317 kg ha −1 , RRMSE 6% compared to RMSE 572 kg ha −1 , RRMSE 11% without assimilation), but only slightly during the second year (RMSE 1961 kg ha −1 , RRMSE 55% compared to RMSE 2019 kg ha −1 , no RRMSE reported), with a strong underestimation of the observed yield.…”
Section: Sentinel-2 Lai Estimationsmentioning
confidence: 99%
“…A range of different observations (either field-measured or derived from remote sensing) have been assimilated into crop models, e.g. phenology [4], soil water content [5][6][7][8], canopy cover [9], and most-prominently used, leaf area index [2,7,8,[10][11][12][13][14][15]. Defined as the total one-sided area of leaf tissue per unit ground surface area, it is one of the key parameters in crop growth analysis because of its influence on light interception, biomass production, plant growth, and ultimately on crop yield, and it is critical to understanding the function of many crop management practices [16].…”
Section: Introductionmentioning
confidence: 99%